1995
DOI: 10.1038/ng0595-41
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a susceptibility locus for schizophrenia on chromosome 6pter–p22

Abstract: We have performed linkage analysis in 186 multiplex families to search for genes that predispose to schizophrenia. Under a model with partially dominant inheritance, moderately broad disease definition and assuming locus homogeneity, a lod score of 3.2 was obtained for D6S260 on chromosome 6p23. A multipoint lod score of 3.9 (P = 2.3 x 10(-5)) was achieved when the F13A1 and D6S260 loci were analysed, allowing for locus heterogeneity. Adjusted for testing of multiple models, the multipoint lod score of 3.9 und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
128
2
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(135 citation statements)
references
References 31 publications
4
128
2
1
Order By: Relevance
“…Large collections of pairs of affected relatives (usually sib pairs) have been studied for a number of complex illnesses, including non-insulin diabetes mellitus, 4,5 prostate cancer, 6 and schizophrenia. 7,8 Alternatively, small sets of large extended pedigrees have been used to study complex diseases such as early-onset Alzheimer's 9 and, most recently, Parkinson's disease. 10 Only a few large multiplex schizophrenia pedigrees are known to exist, 11 primarily because of exceptionally low rates of Correspondence: W Byerley, Department of Psychiatry, University of Utah Medical Center, 50 North Medical Drive, Salt Lake City, Utah 84132, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Large collections of pairs of affected relatives (usually sib pairs) have been studied for a number of complex illnesses, including non-insulin diabetes mellitus, 4,5 prostate cancer, 6 and schizophrenia. 7,8 Alternatively, small sets of large extended pedigrees have been used to study complex diseases such as early-onset Alzheimer's 9 and, most recently, Parkinson's disease. 10 Only a few large multiplex schizophrenia pedigrees are known to exist, 11 primarily because of exceptionally low rates of Correspondence: W Byerley, Department of Psychiatry, University of Utah Medical Center, 50 North Medical Drive, Salt Lake City, Utah 84132, USA.…”
Section: Introductionmentioning
confidence: 99%
“…4 Further analysis in the entire set of 265 families revealed a maximum lod score of 3.51 with marker D6S296 in approximately 15-30% of the families. 13 Several other studies have also found evidence for linkage on the same fairly large chromosomal region.…”
mentioning
confidence: 99%
“…More recently, loci involved in susceptibility to schizophrenia have also been described on chromosome 22 (Pulver et al, 1994a,b;Moises et al, 1995a;Schwab et al, 1995b andGill et al, 1996) and chromosome 6 (6p24-22) delimited by the markers D6S296, D6S285, D6S274, D6S260 and D6S259 (Straub et al, 1995;Schwab et al, 1995a, Moises et al, 1995bWang et al, 1995Wang et al, , 1996, as well as new additional regions on chromosomes 9 and 20 (Moises et al, 1995b) and 3 and 8 . In a study of linkage, using 15 markers covering 30 centimorgans of the 8p22-21 region of chromosome 8p, Kendler et al (1996) suggested that there might be a locus of vulnerability to schizophrenia on this chromosome.…”
Section: Reviewmentioning
confidence: 99%
“…Riley et al (1997) proposed a locus on chromosome 9 (9q34.3), corresponding to the gene for the N-methyl-D-aspartate receptor subunit. Consequently there is in the literature a tendency to admit a heterogeneity of loci (Moises et al, 1995b;Straub et al, 1995;Wang et al, 1995), with Risch (1990) suggesting a group of interacting loci in a "multilocus model". Citing many papers in support, Baron (1996) found "negative or ambiguous results" for a locus predisposing to schizophrenia on chromosome 6 (6p24-22) (Diehl et al, 1994;Mowry et al, 1995;Gurling et al, 1995;Antonarakis et al, 1995;Riley et al, 1995;Sasaki et al, 1995;Moises et al, 1995b), but more recent work (Wang et al, 1996) presents evidence of linkage disequilibrium between schizophrenia and the SCA 1 CAG repeat on chromosome 6p23 (SCA1 = gene for spinocerebellar ataxia type 1).…”
Section: Reviewmentioning
confidence: 99%